Correlation between Body Mass of the Younger School Age Students in Town Schools and the Schoolbag Weight - Živorad М. Marković (University of Belgrade, Teacher Education Faculty, 2018)
The goal of this research was to determine the correlation between the body weight of preparatory preschool children and the weight of their schoolbags in the framework of the standards prescribed by the World Health Organisation and to examine students' attitudes towards schoolbags which they carry every day. The research had a transversal character and it was conducted in the second term of 2015/2016 school year in the preschool institution "Dečija Radost" in Svilajnac. The sample consisted of 90 boys and 90 girls. The results indicate a large span of values of body weight, schoolbag weight and the correlation between the body weight and the preschoolers' schoolbag weight expressed in percentages. The correlation for boys and girls exceeds 10% of the values prescribed by the World Health Organisation. Boys come to school mostly on foot, while girls come to school by car. A schoolbag is carried on both shoulders. In most of the cases parents help their preschoolers to pack the schoolbag. While carrying their schoolbags, pupils feel some pain, mostly in the neck and the back. A heavy bag of preschoolers, and later pupils of younger school age, is not a problem only in Serbia but in the whole world.